Cardiac-sympathetic dysfunction in hypertension - Bardsley, E (2018)
The work presented in this thesis examined the cellular and molecular phenotypes associated with sympathetic over-activity in the initiation and progression of hypertension in the prehypertensive spontaneously hypertensive rat (preSHR) and spontaneously hypertensive rat (SHR), with validation of key molecular pathways in human stellate ganglia. Chapter One provided an overview of the short and long-term regulation of arterial blood pressure. This chapter focussed specifically on the role of the sympathetic nervous system as a primary causative factor in the aetiology of hypertension, and presented evidence highlighting a critical role for impaired cyclic nucleotide signalling in sympathetic over-activity. Chapter Two detailed the methodology utilised in each chapter of this thesis. Specifically, sympathetic neuronal culturing and Förster Resonance Energy Transfer (FRET) were used to measure intracellular cyclic nucleotide generation and protein kinase activity. This chapter also included a comprehensive description of an RNA sequencing analysis pipeline, intracellular Ca2+ imaging, immunofluorescence, protein assays, enzyme activity assays, electrical field stimulation and high-pressure liquid chromatography with electrochemical detection. Chapter Three examined the transcriptome of the stellate ganglia from the SHR compared to its normotensive Wistar counterpart. Differentially expressed genes were reported and individual genes were grouped into gene families and enriched pathways to provide functional relevance. The over-represented molecular function gene ontology families included ligand-gated ion channels and regulation of phosphodiesterase signalling. The expression of key genes was confirmed in human stellate ganglia for physiological context. Chapter Four investigated the role of presynaptic beta-adrenergic signalling as a mediator of elevated neurotransmission in the preSHR stellate ganglia. Neuronal cAMP-PKA-Ca2+ signalling pathways coupled to beta-adrenergic receptors were measured and found to be elevated in prehypertension. The beta-2-adrenoceptor was shown to play a dominant role. The expression of presynaptic beta adrenoceptors was also observed in human stellate ganglia. Chapter Five examined the profile of catecholamines synthesised in the cardiac-sympathetic stellate ganglia of preSHR and their healthy counterparts. Noradrenaline released from the preSHR ganglia was elevated compared to Wistar. Moreover, the synthesis of adrenaline was observed, where the concentration of adrenaline released from the preSHR ganglia was also elevated. The enzyme involved in adrenaline synthesis was observed in human stellate ganglia. Chapter Six highlighted a role for intracrine angiotensin synthesis in the cardiac-sympathetic stellate ganglia of preSHR and SHR alongside their healthy counterparts. The receptors for AngII and Ang1-7 were identified on rat and human stellate ganglia. In preSHR stellate ganglia, the synthesis of AngII and Ang1-7 were elevated, whereas in young preSHR stellates, electrically-evoked concentrations of AngII were not elevated compared to Wistar. In adult SHR stellate ganglia, the synthesis of AngII was elevated, however, the synthesis of the Ang1-7 peptide was no longer increased. This occurred alongside a concomitant elevation in electrically-evoked AngII from adult SHR stellate ganglia. Chapter Seven provided a concluding discussion and summarised the main observations in this thesis with a focus on wider physiological context. Chapter seven also discussed the implications of the findings described, with an emphasis on the potential future avenues of research within the field of neurogenic hypertension.